Rancang Bangun Dinamometer Berbasiskan Strain Gauge Dengan Batang Sensor Tipe Four Square Stalk Untuk Pengukuran Gaya Potong Mesin Bubut - Anwar, Khairul; Yohanes, Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Dynamometer is a measurement instrument that functions to measure the cutting force on a lathe machine. The dynamometer is a measuring of tool that using of a strain gauge sensor of utilizing strain, which occur on the stalk strain as the reader, then it is converted into cutting force. The main purpose of this study is to produce a dynamometer with type four square stalks for cutting force measurement, dynamometer designed to be able tomeasure the axial force and tangential force. The design process consists of designing, manufacturing and calibration processes. The design step is started from material selection, dynamometer selection and dynamometer dimensional design. The dimensions from design is then drawn detail and analyzed stress. After design process is complete, then the process of making the mechanical components and electrical components dynamometer. Afterthat, the dynamometer is assembled for calibration process. The calibration process consists of hysteresis and repeatability errors. This research revealed the hysteresis for maximum tangential force of 1 milivolt and for maximum axial force of 2 milivolt. The repeatability error was 2 milivolt for the maximum tangential force and maximum axial force of 2 milivolt. Dimension of the dynamometer of type four square stalks was a length of 185mm and a diameter of 65 mm. The dynamometer can measure maximum force 500 N for axial and tangential force.Keyword : Dynamometer, Cutting Force, Strain Gauge, Calibration